STUDI KARAKTERISTIK PEJALAN KAKI DAN PEMILIHAN JENIS FASILITAS PENYEBERANGAN PEJALAN KAKI DI KOTA PALU (Studi Kasus: Jl. Emmi Saelan Depan Mal Tatura Kota Palu) - Mashuri, Mashuri; Ikbal, Muhammad (Jurnal REKAYASA dan MANAJEMEN TRANSPORTASI, 2011)
There are many roads in urban areas where the concentration is the traffic flow of vehicles andpedestrians. This condition causes the demanding needs of road widening more and more arefound in the area to smooth flow of vehicular traffic. But on the other hand, attention topedestrian safety is often overlooked. This can be seen from the absence of adequatepedestrian facilities such as a lack of pedestrian facilities in the area of the region which is wherethe concentration of pedestrians and vehicles, pavement condition is not good.The purpose of this study was to determine the characteristics of pedestrian facilities and find outa suitable pedestrian crossing on Jl. Emmi Saelan Tatura Mall in front of Palu City. Data volume ofvehicles and pedestrians have been collected through a survey of traffic. Volume of data trafficcarried on Friday, Saturday and Sunday for 6 hours of peak. Data volume of pedestrians crossingthe road is done by observation segment length of 100 m for 6 hours busy.The study found that the characteristics of pedestrians on Jl. Emmi Saelan at Home Mall TaturaPalu, is dominated by pedestrian age group aged 21-61 years (77.14%), dominated by femalesex (74.29%), type of work is dominated by the student / students (42.86%), education level isdominated by SMA (58.57%) and the purpose of the trip was dominated by shopping (60%). Typea suitable crossing facilities at the study sites based on the value of PV2, P and V is the pedestrianbridge. This means that existing pedestrian facilities in accordance with needs.